Predictors of dental care utilization in north‐central Appalachia in the USA. Issue 4 (17th April 2019) - Chen, Mengxia; Wright, Casey D.; Tokede, Oluwabunmi; Yansane, Alfa; Montasem, Alexander; Kalenderian, Elsbeth; Beaty, Terri H.; Feingold, Eleanor; Shaffer, John R.; Crout, Richard J.; Neiswanger, Katherine; Weyant, Robert J.; et al.
Abstract: Objectives: Dental utilization is an important determinant of oral health and well‐being. The aim of this study was to evaluate potential associations between a variety of biopsychosocial factors and dental utilization in north‐central Appalachia, USA, a region where oral health disparities are profound. Methods: This study used household‐based data from the Center for Oral Health Research in Appalachia (COHRA1) study in north‐central Appalachia, including 449 families with 868 adults. The generalized estimating equation (GEE) approach was used to determine the best‐fitting predictor model for dental utilization among adult family members. Results: On average across West Virginia and Pennsylvania, having dental insurance was associated with greater dental utilization over a 3‐year time period (OR = 2.20, 95% CI = 1.54, 3.14). When stratified by state, the association held for only West Virginia (OR = 2.41, 95% CI = 1.54, 3.79) and was nonsignificant for Pennsylvania residents (OR = 1.50, 95% CI = 0.80, 2.79). Individuals from Pennsylvania were more likely to utilize dental care and participants from West Virginia less so (2.31, 95% CI = 1.57, 3.40). Females from Pennsylvania were more likely than males to regularly seek dental care (OR = 1.44, 95% CI = 1.00, 2.05), and a higher income was associated with greater frequency of regular dental visits (OR = 1.21, 95% CI = 1.09, 1.34) in West Virginia. Individuals from Pennsylvania who scored higher on the Physiological Arousal subscale of the Dental Fear Survey were more likely to attend routine care visits (OR = 1.18, 95% CI = 1.03, 1.35). Across both states, more fatalistic beliefs related to oral health care also predicted less routine care (OR = 0.87, 95% CI = 0.81, 0.94), and more investment in or more positive attitudes towards one's oral health also was associated with higher utilization (OR = 1.18, 95% CI = 1.13, 1.23). Conclusions: Overall, the findings of this study suggest state residency, sex, insurance, income, fatalistic beliefs, health values, and aspects of dental care‐related anxiety and fear predicted dental care utilization in north‐central Appalachia. These findings reinforce the need to address insurance and other economic factors affecting utilization and to consider how individual‐level fatalistic beliefs and oral health values may affect utilization of routine oral health care.